PENGEMBANGAN PLATFORM DIGITAL BERBASIS LINKTREE DENGAN GEOGEBRA “BARSAMA” PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII MTs - Fatchiyah, Fina; Utami, Mutiara Arlisyah Putri (Galois: Jurnal Penelitian Pendidikan Matematika, 2022)
The product developed in this research is a linktree-based digital platform with the geogebra "BARSAMA". This development research aims to determine the validity of the linktree-based digital platform with the “BARSAMA” geogebra. This digital platform is in the form of an application that contains several links that are used in 10 menus. Some of these menus will help in the learning process. This development research uses a 4D development model but only consists of three stages, namely Define (defining), Design (planning), Development (development). The subjects used are validator experts. Data collection techniques are interviews and questionnaires, and the data obtained are quantitative and qualitative. Quantitative data obtained from the validation value. Qualitative data obtained from the criticism and suggestions of the validator. The test results by experts stated that the linktree-based digital platform with the geogebra "BARSAMA" was very feasible with the percentage of material validation being 89.5%, media validation 98%, and learning model validation 87%.